Transformation Practices of Multiliteracy in English Classroom - Laela Hikmah Nurbatra; Sri Hartiningsih (International Journal of English Learning and Applied Linguistics (IJELAL), 2021)
Today's students are digital native generations that heavily rely on the use of technology and social media in their personal, interpersonal and social interaction. Their way of living indeed shapes the way they interact, learn and perform in English learning class. In accordance with that, multiliteracy which is recognized by the use of technology and social media is seen as a ‘bridge' to fill the gap between teachers and the digital native students. The objective of the present research, therefore, is to investigate the implementation of multiliteracy in teaching speaking at SMPN 2 Batu. To answer the research question, the research employs a qualitative research design which uses observation and interviews as the research instruments. The result of the present research revealed that seven practices indicated the integration of multiliteracy in teaching speaking at SMPN 2 Batu. The practices involve the use of pictures and video to support the lesson, the creation of video and poster as the student project, students' exploration of digital tools to edit pictures, the use of online platform to submit the work, the exploration of the internet to facilitate their learning, the exposure of conventional as well as digital text, and lastly, reflection. In addition, there are four challenges experienced by the teaching in multiliteracy at SMPN 2 Batu namely time constraint, limited internet connection or access, passive students and diverse digital skills.